English for Marine Industry Training in PT 4S Marine, Sidoarjo - Dwi Wahyuningtyas; Naajihah Mafruudloh; Zainal Abidin Achmad; Rima Nur Pitasari; Metrya Damayanti; Lusia Ervi Oktaviarika (Fakultas Hukum, UPN Veteran Jawa Timur, 2022)
Indonesia is a maritime and archipelagic country surrounded by seas. As a maritime country, Indonesia has relied on its natural resources from the seas for years. It is also rich in marine resources such as fish, seaweed, shells, and other seafood that become essential trade commodities. This situation makes speedboat as one of the essential things in processing marine resources. It then boosts the establishment of speedboat companies in Indonesia, one of which is PT 4S Marine, located in Sidoarjo. The company started its production in 2016. It produces speedboats, boat fiber, speedboat aluminum, marine equipment, and wooden boats. This company has already received many orders from around Indonesia, and this makes the documents needed are still written in Bahasa Indonesia. However, when the company buys equipment from other countries, it requires filling out some documents written in English. Therefore, the staff in the company needs to learn more about reading and writing documents in English. Besides, the staff also needs to master the communication skills in English. As they also need to communicate with the sellers from other countries. This reason then initiates the community service program held by PIKAT (Pemanfaatan IPTEKS Bagi Masyarakat) of UPN “Veteran” Jawa Timur. From the program that had been run for one month, the team had successfully identified the problems of the staff, especially in writing and speaking in English, and gave the staff training both online and offline. The program continues via the Whatsapp group. In the future, it is expected that the company staff can use English in written and spoken form more fluently so that the company can reach the international market and sell more products to other countries.